PROFIL PENDERITA MORBUS HANSEN (MH) DI POLIKLINIK KULIT DAN KELAMIN BLU RSUP PROF. DR. R. D. KANDOU MANADO PERIODE JANUARI – DESEMBER 2012 - Tiwow, Patricia I.; Kandou, Renate T.; Pandaleke, Herry E. J. (e-CliniC, 2014)
Abstract: Hansen’s Disease is a chronic infection disease caused by Mycobacterium leprae. The transmission of this disease is by direct contact with Hansen’s Disease patients in a long period of time, and by inhalation. This study aimed to evaluate the profile of hansen’s disease patients in Dermatovenereology clinic of Prof. Dr. R. D. Kandou Hospital Manado during the period from January – December 2012. This is a descriptive retrospective study. The result of this study showed that among 112 patients with hansen’s disease, the highest rate was within 25-44 age group (46.4%), where male patients outnumbered females (64.3%). Most of the patients reside in the district of Singkil (12.5%). Multibacillary leprosy was most frequent (89.3%). There were 16% patients with ENL reactions. The disability stage 2 were found in 8,1% patients. Most patients had no history of treatment with MDT (54.5%). Keywords: Hansen’s Disease, profile.   Abstrak: Morbus Hansen (MH) adalah penyakit infeksi kronik yang disebabkan oleh Mycobacterium leprae. Penularan terjadi melalui kontak langsung dalam jangka waktu yang lama dan melalui inhalasi. Penelitian ini bertujuan untuk mengetahui profil penderita morbus hansen di poliklinik kulit dan kelamin BLU RSUP Prof. Dr. R.D. Kandou Manado periode Januari-Desember 2012. Penelitian bersifat deskriptif retrospektif. Hasil penelitian memperlihatkan dari 112 penderita MH (10,22%) terbanyak berasal dari kelompok umur 25-44 tahun (46,4%), jenis kelamin laki-laki (64,3%), tempat tinggal kecamatan Singkil (12,5%), tipe MH terbanyak tipe Multibasiler (89,3%), terdapat reaksi ENL sebanyak 16%, kecacatan tingkat 2 sebanyak 8,1%, dan riwayat pengobatan terbanyak belum pernah melakukan pengobatan MDT sebelumnya (54,5%). Kata Kunci: Morbus Hansen, profil.